Analysis of organizational culture and climate for fast moving consumer goods in company X Bandung branch - Effendy, Amalia Syafira; Lestari, Martha Tri (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
Organizational culture serves as the foundation of shared values and beliefs, significantly influencing the formation of organizational climate. Effective organizational communication contributes to a positive work environment, ultimately impacting employee performance and satisfaction. This study aims to analyze how organizational culture shapes the corporate climate in an FMCG company’s Bandung branch. Using a qualitative approach within an interpretive paradigm, this research explores how the company’s core values integrity, collaboration, innovation, respect, and excellence affect employees' perceptions of their work environment. Data collection techniques include literature review, observation, and in-depth interviews with employees across different organizational levels. The findings reveal that a strong organizational culture, characterized by open communication and a trust-based work system, plays a crucial role in fostering a positive organizational climate. The absence of a formal attendance system in this company demands high levels of responsibility and honesty among employees, reinforcing their sense of ownership towards the company. Additionally, an informal yet professional work relationship enhances collaboration and innovation among employees. With a flexible and creativity-driven work culture, the company successfully establishes a positive organizational climate that boosts employee motivation and productivity. Amidst the intensifying competition in the FMCG industry, these findings offer valuable insights for companies in managing their organizational culture to maintain competitive advantage. This study also provides practical implications for organizations seeking to implement their workplace culture and climate.